Materials for bicycle frame system - a case study on the development of selection method - Maleque, Md. Abdul; Sarker, Dyuti (2010)
The selection of the correct materials for a design is a key step in the process because it is the crucial decision that links computer calculations and lines on an engineering drawing with a working design. Materials, and manufacturing processes which convert the material into a useful part, underpin all of engineering design. In the relation of design stages and process selection with material selection, screening and ranking are two vital steps in the material selection. This paper will present the contribution of the development of material selection method using Ashby’s for material selection charts for the application of bicycle frame system. Two methods such as, cost per unit strength and digital logic method are identified. The properties such as mechanical properties, including tensile strength, yield strength, Young’s modulus, toughness, density as well as cost, were considered as the key parameters in the material selection methods. The candidate materials are found to be AISI 1020 steel, Ti alloys, CFRP, KFRP and GFRP for bicycle frame system. The final analysis was led to the KFRP as the most appropriate material for bicycle frame.